Tacitus, the epic successor : Virgil, Lucan, and the narrative of civil war in the histories - Joseph, Timothy A. (Mnemosyne, Supplements, 2012)
Allusions to the epic poets Virgil and Lucan in the writing of the Roman historian Tacitus (c. 55 - c. 120 C.E.) have long been noted. This monograph argues that Tacitus fashions himself as a rivaling literary successor to these poets; and that the emulative allusions to Virgil's Aeneid and Lucan's Bellum Civile in Books 1-3 of his inaugural historiographical work, the Histories , complement and build upon each other, and contribute significantly to the picture of repetitive, escalating civil war in the work. The argument is founded on the close reading of a series of related passages in the Histories , and it also broadens to consider certain narrative techniques and strategies that Tacitus shares with writers of epic.